Sensitive Wearable Temperature Sensor with Seamless Monolithic Integration. Issue 2 (7th November 2019) - Shin, Jaeho; Jeong, Buseong; Kim, Jinmo; Nam, Vu Binh; Yoon, Yeosang; Jung, Jinwook; Hong, Sukjoon; Lee, Habeom; Eom, Hyeonjin; Yeo, Junyeob; Choi, Joonhwa; Lee, Daeho; et al.
Abstract: Accurate temperature field measurement provides critical information in many scientific problems. Herein, a new paradigm for highly sensitive, flexible, negative temperature coefficient (NTC) thermistor‐based artificial skin is reported, with the highest temperature sensing ability reported to date among previously reported NTC thermistors. This artificial skin is achieved through the development of a novel monolithic laser‐induced reductive sintering scheme and unique monolithic structures. The unique seamless monolithic structure simultaneously integrates two different components (a metal electrode and metal oxide sensing channel) from the same material at ambient pressure, which cannot be achieved by conventional heterogeneous integration through multiple, complex steps of photolithography or vacuum deposition. In addition to superior performance, electronic skin with high temperature sensitivity can be fabricated on heat‐sensitive polymer substrates due to the low‐temperature requirements of the process. As a proof of concept, temperature‐sensitive artificial skin is tested with conformally attachable physiological temperature sensor arrays in the measurement of the temperatures of exhaled breath for the early detection of pathogenic progression in the respiratory system. The proposed highly sensitive flexible temperature sensor and monolithic selective laser reductive sintering are expected to greatly contribute to the development of essential components in various emerging research fields, including soft robotics and healthcare systems. Abstract : A highly sensitive and fast‐responding monolithically integrated flexible temperature sensor is demonstrated by developing a novel laser thermal process on a thin polymer substrate. The temperature sensor is applied on the face, nasal cavity, and robotic hand to detect a physiological signal or regenerate vivid thermal sensations. The temperature sensor has the potential for temperature‐sensitive E‐skin, soft robotics, and versatile temperature sensing applications.